Protective Effect of Berberine on Acute Gastric Ulcer by Promotion of Tricarboxylic Acid Cycle-Mediated Arachidonic Acid Metabolism - Guo Q; Lu T; Zhang M; Wang Q; Zhao M; Wang T; Du M (Dove Medical Press, 2024)
Qiuyan Guo,1,2,* Tianming Lu,1,3,* Min Zhang,4,* Qixin Wang,1,2 Minghong Zhao,2,5 Tongchun Wang,6 Maobo Du1 1Institute of Chinese Materia Medica, China Academy of Chinese Medical Sciences, Beijing, 100700, People's Republic of China; 2Artemisinin Research Center and Institute of Chinese Materia Medica, China Academy of Chinese Medical Sciences, Beijing, 100700, People's Republic of China; 3Department of Epidemiology and Health Statistics, School of Public Health, Guangxi Medical University, Nanning, Guangxi, 530021, People's Republic of China; 4Institute of Basic Theory for Chinese Medicine, China Academy of Chinese Medical Sciences, Beijing, 100700, People's Republic of China; 5Laboratory Medicine, Guizhou Aerospace Hospital, Zunyi, Guizhou, 563000, People's Republic of China; 6Traditional Chinese Medicine Orthopedics and Traumatology Department, Shandong Wendeng Orthopedic Hospital, Wendeng, Shandong, 264400, People's Republic of China*These authors contributed equally to this workCorrespondence: Maobo Du, Institute of Chinese Materia Medica, China Academy of Chinese Medical Sciences, Beijing, 100700, People's Republic of China, Email mbdu@icmm.ac.cnBackground and Objective: Peptic ulcer is a high incidence gastrointestinal disease in China. Berberine (BBR) is a natural product isolated from the Chinese herb Coptis chinensis Franch that has protective effects in digestive diseases. We aimed to evaluate the ability of BBR to attenuate acute gastric ulcer induced by one-time administration of ethanol in the rat.Methods: Tissue pathological morphology, macroscopic score, ulcer healing rate, and serum levels of the inflammatory cytokines nitric oxide (NO), interleukin-6 (IL-6), and prostaglandin E2 (PGE2), and anti-inflammatory interleukin-10 (IL-10) were used to determine the efficacy of BBR and evaluated to identify the optimal dosage. Subsequently, transcriptome and metabolome sequencing were conducted in Control, Model, and optimal dosage groups to explore the pathogenesis of the disease and the mechanism of action of the drug. The levels of malondialdehyde (MDA), myeloperoxidase (MPO), as well as those of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were determined by enzyme-linked immunosorbent assay to verify the results of transcriptomics and metabolomics analyses.Results: BBR significantly improved the pathological morphology of gastric ulcers, increased the macroscopic score and healing rate, decreased serum levels of NO, IL-6, and PGE2, and increased serum levels of IL-10, thus effectively alleviating gastric ulcer severity. Transcriptome results showed that the therapeutic effect of BBR was mainly mediated by the arachidonic acid metabolism pathway at the gene level, which is closely associated with inflammation and increased levels of reactive oxygen species (ROS). The differentially accumulated metabolite prostaglandin E1, which is a negative regulator of ROS, was significantly up-regulated after BBR administration. The validation results indicated that BBR pretreatment increased SOD and GSH-Px enzyme activities, while reducing levels of the oxidative products MDA and MPO.Conclusion: This study demonstrated that BBR exerts a protective effect on acute gastric ulcer by promoting tricarboxylic acid cycle-mediated arachidonic acid metabolism. Keywords: Berberine, acute gastric ulcer, transcriptome, untargeted metabolomics